ANALISIS PENGARUH LABELISASI HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCAREDI KOTA TIMIKA - Anggi Anggraeni; Muh.Sabir (CV. Adiba Aisha Amira, 2025)
This study aims to determine the Effect of Halal Labeling and Price on Purchasing Decisions for Skincare Products in Timika City. The method used in this study is the associative method. Data collection techniques used in this study are observation and data collection sheets (questionnaires). The analysis tool used in this study is multiple linear regression with data processing techniques, namely classical assumption tests and hypothesis tests, to analyze data using SPSS 25 for Windows software. The results of the study indicate that halal labeling and price have a positive and significant effect on purchasing decisions for skincare products in Timika City.